Margin Status Impacts Survival after Pancreaticoduodenectomy but Negative Margins Should Not be Pursued. Issue 4 (April 2014) - Mathur, Abhishek; Ross, Sharona B.; Luberice, Kenneth; Kurian, Tony; Vice, Michelle; Toomey, Paul; Rosemurgy, Alexander S.
Negative margins are the goal with pancreaticoduodenectomy for pancreatic adenocarcinoma. Thereby, margins are assessed intraoperatively with frozen section analysis and negative margins are pursued. This study was undertaken to determine the impact of margin status with pancreaticoduodenectomy for pancreatic adenocarcinoma and the value of extending resections to achieve negative margins. The intraoperative frozen section analysis and final margins for 448 patients undergoing pancreaticoduodenectomy for pancreatic adenocarcinoma were assessed and their impact on survival was determined. Median data are presented. Two hundred ninety-eight (67%) patients had negative margins (R0), an additional 110 (25%) patients had microscopically positive and macroscopically negative margins (R1), and an additional 40 (9%) patients had initially positive microscopic margins, which became negative with further resection (R1 å R0). R0 resections were more likely to have smaller tumors, earlier T grade, earlier N grade, lower American Joint Committee on Cancer stage, and less frequent extrapancreatic extension ( P ≤ 0.03 for each). Survival was better with R0 resections than R1 resections (20 vs 12 months, P < 0.001); extending resections to achieve negative margins (i.e., R1 ! R0) did not improve survival beyond R1 resections (14 vs 12 months, P = 0.19). Survival after pancreaticoduodenectomy is disappointing. Patients with initial negative margins do best. Positive microscopic margins reflect more aggressive tumor-specific factors and lead to abbreviated survival even with extended resections to achieve negative margins (i.e., R1 ! R0). With an initial positive margin, pursuing negative margins does not improve survival and, thereby, negative margins should not be "chased."